Amoris Laetitia: die Eröffnung der "kulturellen Rezeption" des II. Vatikanischen Konzils durch das Magisterium - Hünermann, Peter (Zeitschrift für katholische Theologie, 2017)
The article begins by recalling Jan Assmann's view of »cultural reception« as a process by which historical events and memories of them pass into the selfunderstanding of a society and thus gain a symbolic quality and pithiness that helps define this self-understanding. It then argues that Amoris Laetitia is instrumental in passing the historical reception of the Second Vatican Council into the cultural reception of the church. Among other examples a renewal of the theology of marriage and family stands out as an example.